Optimalisasi Penggunaan Media Sosial Sebagai Alat Pemasaran Digital untuk Meningkatkan Penjualan Es Teh Desa - Tama, Ermalia Wahyu Dwi; Ningsih, Widia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the role of social media in increasing consumer loyalty to the Es Teh Desa brand. In the digital era, social media has become an important means of establishing relationships with consumers. The purpose of this service is to improve and motivate business owners to improve marketing performance through social media. This study uses a quantitative approach, namely an approach by collecting data and information from various sources such as scientific journals and trusted online sources that are relevant to the topic discussed. The results of the study show that the use of social media, especially Instagram and TikTok, has a significant influence on increasing engagement, brand awareness, and consumer loyalty. Promotional strategies on social media to increase product excellence and develop public interest in Es Teh Desa. Help consumers explain the flavor variants available on the Es Teh Desa menu that is sold. Promotional strategies can expand promotional targets, make it easier to receive direct feedback, and can compete with other competitors. The results of promotions through social media can facilitate promotions effectively and efficiently, so that they can increase sales at Es Teh Desa.